Identifying immunoreactive proteins in brucellin for enhanced brucellosis diagnosis: a proteomic approach - Krasteva, Ivanka; Luciani, Mirella; D’Onofrio, Federica; Di Febo, Tiziana; Di Pancrazio, Chiara; Perletta, Fabrizia; Maggetti, Marta; Ulisse, Simonetta; Sonsini, Luigina; Orsini, Gianluca; Caporale, Marco; Ponsart, Claire; et al. (Frontiers in Microbiology, 2025)
The brucellin skin test (BST) detects brucellosis in animals through a cell-mediated immune response to a protein extract from B. melitensis strain 115, which is almost free of lipopolysaccharide. It is highly specific and used to confirm suspected false positive serology results in small ruminants and swine, but not recommended for screening due to low sensitivity. Despite its diagnostic significance, the protein composition of brucellin has not been fully characterized. This study used nLC-ESI-MS/MS analysis and bioinformatics tools to evaluate brucellin’s protein composition and identify immunoreactive proteins. An allergen suspension of purified proteins (free of S-LPS) of EU Standard Brucellin, produced by ANSES, IZS-Teramo (IZSAM) and the former commercialised brucellergene OCB® were used. Proteomic analysis identified 247 (ANSES), 542 (IZSAM) and 183 (OCB) proteins. Two hundred and six proteins (ANSES), 458 proteins (IZSAM) and 156 (OCB) were predicted as potential antigens, and 123 proteins are common to all 3 brucellins examined. Among the 123 proteins common to all three brucellin formulations examined, several key immunodominant proteins previously identified in Brucella research—such as ribosomal L7/L12, outer membrane protein BP26/OMP28, GroEL, and Bacterioferritin—were consistently detected. Their presence across all formulations supports their important role in inducing delayed hypersensitivity and contributing to Brucella pathogenesis. These findings underscore the importance of introducing mass spectrometry analyses as quality control for brucellin batches production and the potential of these proteins as candidates for detecting cellular immunity against Brucella. Developing recombinant Brucella-allergenic proteins could help in standardizing skin tests, providing reliable allergens favoring disease control and eradication. Moreover, a serological test using these recombinant proteins could improve specificity of current indirect tests for Brucella and eliminate false-positive results associated with LPS-based diagnostics.